FRI0336 Efficacy of tocilizumab in 31 patients with giant cell arteritis. (15th June 2017) - Domínguez-Casas, LC; Loricera, J; Hernández, JL; Castañeda, S; Mera, A; Pérez-Pampín, E; Peirό, E; Humbría, A; Calvo-Alén, J; Aurrecoechea, E; Narváez, J; Sánchez-Andrade, A; et al.
Abstract : Background: Giant cell arteritis (GCA) is often a disease refractory to corticosteroids and, besides, the efficacy of immunosuppressive agents is not well established. In recent years, several case reports and small case series have shown efficacy with the use of tocilizumab (TCZ). Objectives: Our aim was to assess in a clinical practise setting the short and long-term efficacy of TCZ in GCA patients with refractory disease and/or with unacceptable side effects due to corticosteroids. Methods: Retrospective multicenter open-label study on 31 GCA patients treated with TCZ [intravenously at standard dose of 8 mg/kg/monthly (n=29), and subcutaneously at a dose of 162 mg/week (n=2)]. We assessed the efficacy on clinical and laboratory parameters, the reduction of the dose of corticosteroids, as well as the short and long-term side effects and the possibility of discontinuation or reduction of the dose of TCZ. Wilcoxon test was used to compare laboratory parameters across time. Results: We included 31 patients (24 women/ 7 men), with a mean age of 73±9 years. The main clinical features at TCZ onset were: polymyalgia rheumatica (n=21), asthenia (n=8), headache (n=8), constitutional syndrome (n=11), jaw claudication (n=3), and visual loss (n=4). Besides corticosteroids and before TCZ onset, 26 patients had also received several conventional immunosuppressive and/or biologic drugs. Twenty-seven of 31 patients achieved a rapid and maintained clinical improvement after TCZ therapy (Table). After a median follow-up of 18 [interquartile range, 6–30] months we observe a reduction of the median of: a) CRP from 1.9 [1.1–3.7] to 0.1 [0.1–0.7] mg/dL; b) ESR from 44 [17–74] to 12 [4–16] mm/1st hour; and c) the dose of prednisone from 20 [10–45] to 2.5 [0–7.5] mg/day. In this follow-up period, the outcome of patients was as follows: a) discontinuation of TCZ (n=8) due to sustained remission; b) dose reduction due to improvement (n=5) or side effects (n=2); c) withdrawal of TCZ because of side effects (n=7); and d) the same dose that at onset (n=8). The reasons why TCZ had to be discontinued were: severe neutropenia; recurrent pneumonia; colon adenocarcinoma; cytomegalovirus infection; hypertensive crisis during infusion; myelodysplastic syndrome; and overall health deterioration. The latter patient died because of stroke. Another patient also died after the second TCZ infusion due to stroke in the context of an infective endocarditis. Conclusions: TCZ therapy leads to a rapid and maintained improvement in patients with refractory GCA and/or with unacceptable side effects related to corticosteroids. However, the risk of neutropenia and infection should be kept in mind when using this biologic agent in patients with GCA. Disclosure of Interest: None declared